ADOPSI INFORMASI, ANTESEDEN DAN PENGARUHNYA PADA NIAT BELI: STUDI TENTANG E-WOM DI MEDIA SOSIAL - Fironika Kurnia Novi; Jeanne Ellyawati (Universitas Nusa Cendana, 2021)
High consumer purchasing intentions are one of the factors that support the success of a business. In this digitalization era, the delivery of information through social media is one way to support the success of a business. The requirements that must be met in the delivery of such information are the quality of information, the credibility of information, the need for information, the attitude to information. Good, credible, needed information and good audience attitude support on information will provide usefulness and be adopted by the audience as a reference for their purchase decision making.This research was conducted with the aim of knowing: 1) The influence of information quality, credibility of information, need for information, and attitude on information to the usefulness of information.2) The effect of the usefulness of information on the adoption of information, and. 3) Influence of attitude on information and adoption of information on purchase intention. The study was conducted on 150 respondents. Data collection method using questionnaire and data measurement mentode using Likert scale. The method of data analysis used is regression analysis. The results provide tangible evidence that: 1) The quality of information, the credibility of information, the need for information, and attitudes to information have a significant and positive influence on the usefulness of information. 2) The usefulness of information has a significant and positive influence on the adoption of information, and. 3) Attitudes on information and the adoption of information have a significant and positive influence on the intention of purchase. Keywords: Information Quality, Information Credibility, Need for Information, Attitude to Information, Usefulness of Information, Adoption of Information, Purchase Intention.